Silk fibroin skin protective agent and application
By providing physical and chemical protection through silk fibroin skin protectants, skin damage during radiotherapy is reduced. The film-forming properties and antioxidant components of silk fibroin improve the skin barrier function, meeting the nursing needs of different clinical stages and solving the nursing challenges of radiation dermatitis.
Patent Information
- Application Number
- CN202511649599.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-12
- Publication Date
- 2026-01-30
AI Technical Summary
For skin damage caused by radiation therapy, especially radiation dermatitis, current technologies struggle to provide effective physical and chemical protection, reduce reactive oxygen species-related damage, and meet the care needs of different clinical stages and skin conditions.
It uses a silk fibroin skin protectant, which contains silk fibroin, a complex inorganic protectant, titanium dioxide and silicon dioxide or zinc oxide particles, antioxidants and moisturizers, to form a flexible film that provides physical protection, antioxidant and moisturizing functions. It is suitable for dosage forms such as creams, gels and films.
It reduces skin damage during radiotherapy, promotes moist healing, reduces damage to the skin from ultraviolet radiation and reactive oxygen species, and improves skin barrier function. It is suitable for radiotherapy patients at different stages.
Smart Images

Figure CN121422191A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of medical aesthetics technology, specifically to a silk fibroin skin protectant and its application. Background Technology
[0002] Radiation therapy for tumors is a local treatment method that uses radiation to treat tumors. Approximately 70% of cancer patients require radiation therapy during their cancer treatment, and about 40% of cancers can be cured with radiation therapy. The role and importance of radiation therapy in cancer treatment is increasingly prominent, and it has become one of the main methods for treating malignant tumors. The efficacy of radiation therapy depends on radiosensitivity; different tissues and organs, as well as various tumor tissues, react differently after being irradiated. Therefore, keeping the irradiated site clean and preventing infection and necrosis are important conditions for improving radiosensitivity.
[0003] Radiation dermatitis is an inflammatory condition of the skin and mucous membranes caused by radiation exposure. It is primarily seen in patients undergoing radiation therapy and those working with inadequate radiation protection. It can cause a series of skin reactions and damages, including reversible hair loss, dermatitis, pigmentation, and irreversible skin atrophy, damage to sebaceous and sweat glands, permanent hair loss, and even radiation necrosis, subsequently leading to ulceration.
[0004] I. Clinical Manifestations 1. Acute radiation dermatitis Caused by one or more radiation exposures, even relatively low doses can trigger the disease in sensitive individuals. The incubation period varies from 8 to 20 days, depending on the radiation dose and individual tolerance. It can be divided into three degrees: (1) Grade I: Initially bright red, later turning into dark red spots, or with mild edema. Patients experience burning and itching. Desquamation and pigmentation appear after 3 to 6 weeks.
[0005] (2) Grade II: Significant acute inflammatory edematous erythema, with a tense and shiny surface, vesicles forming, which rupture to form erosions. Patients experience burning or pain. It heals in 1 to 3 months, leaving behind pigmentation, depigmentation, telangiectasia, and skin atrophy.
[0006] (3) Grade III: Erythema and edema are followed by rapid tissue necrosis, eventually forming a persistent ulcer. The depth of the ulcer is variable, generally penetrating the skin and muscle, and even bone tissue. The base of the ulcer has a dirty yellowish-white mass of necrotic tissue, and the patient experiences severe pain. It is difficult to heal, and after healing, it forms atrophic scars, pigmentation, depigmentation, and telangiectasia. In severe cases, large blood vessels become occluded, and dry gangrene develops in the limb. Secondary cancerous changes can occur on the ulcers and scars.
[0007] Grade II and III cases may be accompanied by systemic symptoms such as headache, dizziness, lethargy, loss of appetite, nausea, vomiting, abdominal pain, diarrhea, bleeding, and decreased white blood cell count. In severe cases, it can be life-threatening.
[0008] 2. Chronic radiation dermatitis Most cases are caused by long-term, repeated exposure to low-dose radiation, or develop from acute radiation dermatitis. The incubation period can range from several months to decades. Inflammatory manifestations are not obvious. Radiation damages sebaceous glands, sweat glands, hair follicles, and the germinal layer cells of the nail bed, resulting in dry, rough, and cracked skin, hair loss, dull nail color, longitudinal ridges, pigmentation and thickening, and even nail loss.
[0009] II. Local treatment and nursing care 1. Acute radiation dermatitis: Calamine lotion can be used for grade I and II erythema and edema. For acute dermatitis without edema and exudation, as well as chronic dermatitis, mild and non-irritating creams or ointments can be used, such as vitamin E cream, 10% cod liver oil ointment, and other skin creams. Corticosteroid creams or ointments can also be used. Silk fibroin skin protectants, based on the above mild and non-irritating creams or ointments, add silk fibroin, avoiding corticosteroids. This not only enhances moisturizing care but also reduces local inflammation and itching, creates a moist healing environment, reduces pain, and protects the wound.
[0010] 2. Chronic radiation dermatitis: Silk fibroin skin protectant can protect fragile skin and prevent damage and ulceration. Strengthen moisturizing and strictly protect against sun exposure. Strict sun protection is essential during and for at least one year after radiotherapy. Both silk fibroin and titanium dioxide in the silk fibroin skin protectant have sun protection properties, eliminating the need for additional sunscreens and protecting damaged skin from further deterioration. Summary of the Invention
[0011] Technical problems to be solved
[0012] To address the shortcomings of existing technologies, the objective of this invention is to provide a silk fibroin skin protectant and its application, aiming to: Provides both physical and chemical protection to the irradiated areas during radiotherapy, reducing further damage to the skin; By reducing the photocatalytic activity of inorganic particles and adding antioxidants, the damage related to reactive oxygen species during radiotherapy can be mitigated. By utilizing the film-forming and healing properties of silk fibroin, it can improve skin barrier function, maintain skin moisture content, and promote moist healing. We offer a variety of dosage forms (creams, gels, patches, sprays, etc.) suitable for radiotherapy patients to meet the needs of different clinical stages and skin conditions.
[0013] To address the shortcomings of existing technologies, the objective of this invention is to provide a silk fibroin skin protectant and its application, aiming to: Provides both physical and chemical protection to the irradiated areas during radiotherapy, reducing further damage to the skin; By reducing the photocatalytic activity of inorganic particles and adding antioxidants, the damage related to reactive oxygen species during radiotherapy can be mitigated. By utilizing the film-forming and healing properties of silk fibroin, it can improve skin barrier function, maintain skin moisture content, and promote moist healing. We offer a variety of dosage forms (creams, gels, patches, sprays, etc.) suitable for radiotherapy patients to meet the needs of different clinical stages and skin conditions.
[0014] To address the shortcomings of existing technologies, the objective of this invention is to provide a silk fibroin skin protectant and its application, aiming to: Provides both physical and chemical protection to the irradiated areas during radiotherapy, reducing further damage to the skin; By reducing the photocatalytic activity of inorganic particles and adding antioxidants, the damage related to reactive oxygen species during radiotherapy can be mitigated. By utilizing the film-forming and healing properties of silk fibroin, it can improve skin barrier function, maintain skin moisture content, and promote moist healing. We offer a variety of dosage forms (creams, gels, patches, sprays, etc.) suitable for radiotherapy patients to meet the needs of different clinical stages and skin conditions.
[0015] Technical solution
[0016] To achieve the above objectives, the present invention provides the following technical solution: a silk fibroin skin protectant, comprising the following components by mass percentage: Silk fibroin or silk fibroin micron or nano-sized particles, 0.01%–0.5%; Stearic acid 1%–15%; Lanolin 1%–15%; Polyethylene glycol 400-1%~15%; Triethanolamine 0.1%–2%; Dimethicone oil 0.5%–10%; The composite inorganic protective agent is 1% to 25%, wherein the composite inorganic protective agent is a core-shell type or composite particle formed by titanium dioxide as the core and coated with silicon dioxide or zinc oxide, and the particle size range is 10 to 800 nanometers. The antioxidant active ingredient is 0.01% to 2%, wherein the antioxidant active ingredient is tea polyphenols, vitamin E or their derivatives; Moisturizing and barrier repair aids at 0.01%–2%, wherein the aids are sodium hyaluronate, ceramide, glycerin, or a combination thereof; Preservatives, including methylparaben (0.01%–0.2%) and propylparaben (0.01%–0.2%); The remainder is water, which keeps the pH of the formulation between 5.0 and 8.0.
[0017] Preferably, the silk fibroin is natural silk fiber obtained by degumming mulberry silk, or regenerated silk fibroin obtained by dissolving, dialysis and regeneration steps, and preferably exists in the form of particles with an average particle size of 50 to 300 nanometers.
[0018] Preferably, the antioxidant active ingredient is one or more of tea polyphenols, epigallocatechin gallate, quercetin, or vitamin E.
[0019] Preferably, it further contains 0.01% to 1% ceramide or sodium hyaluronate to enhance skin barrier repair and moisturizing properties.
[0020] Preferably, the composite inorganic protective agent has a core-shell structure, with titanium dioxide as the core and silicon dioxide or zinc oxide as the shell, the shell thickness being 5-50 nanometers. The surface of the titanium dioxide is treated with an organosilane coupling agent to reduce photocatalytic activity. By binding acid-sensitive or temperature-sensitive polymer materials to the surface of silk fibroin particles, the active ingredients are released in a sustained manner, thereby prolonging the protective effect time.
[0021] Preferably, the mass percentage of silk fibroin in the protective agent is 0.03% to 0.1%.
[0022] Preferably, a method for preparing a silk fibroin skin protectant includes the following steps: Sp1. Silkworm cocoons are boiled in a sodium carbonate aqueous solution to remove the gum and obtain fibroin; Sp2. After dissolving silk fibroin in lithium bromide solution, dialyze to remove residual salts and concentrate to the desired solid content; Sp3. Silk fibroin nanoparticles are formed by adding an antisolvent to a silk fibroin solution, and natural cross-linking agents are added if necessary; Sp4. Prepare composite particles with titanium dioxide core and silicon dioxide or zinc oxide shell, and control the shell thickness under alkaline conditions; Sp5. Disperse the silk fibroin nanoparticles obtained in step Sp3 and the composite particles obtained in step Sp4 in an aqueous phase, emulsify them with the oil phase, and adjust the pH to form a cream or gel. Sp6. Add antioxidants, preservatives and moisturizing agents at a temperature below 40 degrees Celsius, mix well and obtain the finished product.
[0023] Preferably, the silk fibroin skin protectant is used to block ultraviolet radiation, reduce damage to the skin from reactive oxygen free radicals, repair the skin barrier, and maintain skin moisture content. The silk fibroin skin protectant is used in creams, sprays, patches, gels, or other topical skin protectant preparations.
[0024] Beneficial effects
[0025] This invention provides a silk fibroin skin protectant and its application. It has the following beneficial effects: 1. The composite inorganic particles used in this invention provide physical shielding and scattering effects, reducing the direct stimulation of the wound surface by external ultraviolet rays and other light waves; coating titanium dioxide with silicon dioxide or zinc oxide and modifying its surface can significantly reduce the potential risk of generating reactive oxygen species under light irradiation. 2. The silk fibroin used in this invention exists in the form of nanoparticles, which can form a flexible film on the skin surface, moisturize and provide a scaffold for skin regeneration, which is beneficial to epithelial regeneration and wound repair; the antioxidant components can neutralize free radicals caused by radiation or light, reduce oxidative stress and alleviate inflammatory response; the moisturizing and barrier repair aids work synergistically with the silk fibroin to maintain the hydration of the stratum corneum, reduce transepidermal water loss and promote moist healing; the combined effect can reduce pain, itching and inflammation, shorten healing time and reduce the risk of severe necrosis or intractable ulcers. Attached Figure Description
[0026] Figure 1 The test system of the present invention Figure 1 ; Figure 2 The test system of the present invention Figure 2 ; Figure 3 The test system of the present invention Figure 3 ; Figure 4 The test system of the present invention Figure 4 . Detailed Implementation
[0027] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Specific Implementation Example 1
[0029] A silk fibroin skin protectant, comprising the following components by mass percentage: 0.01%–0.5% silk fibroin or silk fibroin micron or nano-sized particles; 1%–15% stearic acid; 1%–15% lanolin; 1%–15% polyethylene glycol 400; 0.1%–2% triethanolamine; 0.5%–10% dimethicone; and 1%–25% composite inorganic protectant, wherein the composite inorganic protectant is a core-shell type or composite particle with titanium dioxide as the core and coated with silicon dioxide or zinc oxide, and the particle size range is 10 mm. ~800 nm; antioxidant active ingredients 0.01%~2%, the antioxidant active ingredients being tea polyphenols, vitamin E or their derivatives; moisturizing and barrier repair aids 0.01%~2%, the aids being sodium hyaluronate, ceramide, glycerin or their combinations; preservatives, including methylparaben 0.01%~0.2% and propylparaben 0.01%~0.2%; the balance being water, maintaining the pH of the formulation between 5.0 and 8.0; defining the overall composition and basic ratio range of the complex skin protectant.Silk fibroin or its micron / nano particles (0.01%–0.5%) are preferably made from regenerated silk fibroin, derived from silkworm cocoons through degumming, dissolution, dialysis, and regeneration. It is preferred to exist in particulate form to enhance film-forming properties and local retention. The particle size is recommended to be controlled within the range of 50–300 nanometers. The particle size can be controlled by anti-solvent precipitation or ultrasonic atomization. The particle size distribution index is measured using the average particle size and polydispersity index, determined by dynamic light scattering. Stearic acid (1%–15%) serves as an oil-phase solid fatty acid, providing thickening, forming a semi-solid matrix, and participating in emulsification reactions. Its quality grade should meet the standards for external raw materials. The free acid content should be controlled; lanolin (1%–15%) is used to replenish the skin's lipid layer and improve emollient properties and skin compatibility of the formulation. Refined lanolin should be used to reduce impurities and odor; polyethylene glycol 400 (1%–15%) is used as a solubilizer and lubricant for both the aqueous and oil phases, adjusting the feel and viscosity of the formulation; triethanolamine (0.1%–2%) is used to neutralize fatty acids to form an emulsion system and adjust the pH. The amount added should be based on a final pH of 5.0–8.0; dimethicone (0.5%–10%) is an important component for forming a smooth, sealed protective layer, filling fine lines, and reducing water loss. Topical grade dimethicone should be selected, and attention should be paid to… Excessive amounts should be avoided in the formulation to prevent affecting breathability; the composite inorganic protective agent (1%–25%) consists of titanium dioxide core coated with silica or zinc oxide core-shell or composite particles. This component is key to achieving physical protection and avoiding photocatalytic side effects in this formulation. The particle size ranges from 10 to 800 nanometers, preferably 15–200 nanometers to balance light-blocking properties and skin safety; the antioxidant active ingredient (0.01%–2%) is a combination of water-soluble tea polyphenols (such as epigallocatechin gallate) and / or fat-soluble vitamin E (tocopherol or its esters) to cover different free radical scavenging mechanisms. Water-soluble components are preferentially added to the aqueous phase or sealed in the water phase. The formulation is encapsulated in silk fibroin nanoparticles to enhance stability. Moisturizing and barrier repair aids (0.01%–2%) include sodium hyaluronate, ceramides, and glycerin. The recommended molecular weight of sodium hyaluronate is between 50,000 and 2,000,000 Daltons, selected based on film-forming and penetration requirements. Preservatives are a combination of methylparaben and propylparaben to achieve broad-spectrum antibacterial properties, with a content controlled between 0.01% and 0.2%. The formulation must undergo preservative efficacy testing to confirm effectiveness. Deionized water or purified water meeting pharmaceutical / cosmetic water standards is used, and microbial limits and metal residues are controlled during preparation. The overall pH of the formulation is in the range of 5.0–8.0, adjusted to the target range through the neutralization reaction of triethanolamine and fatty acids, and the pH is confirmed in the final product.
[0030] Degumming of mulberry silk can be achieved by boiling in a sodium carbonate aqueous solution (0.02%–0.5% by mass) at 85–95°C for 30–60 minutes, or by using a mild enzymatic degumming method (such as alkaline protease) to minimize damage to the molecular weight of the silk fibroin. After degumming, the silk is thoroughly washed with water until neutral and then dried or directly proceeded to the dissolution step. Dissolution is preferably achieved by dissolving in a lithium bromide solution (approximately 9.3 mol / L) at 60–80°C for 2–4 hours to obtain a homogeneous silk fibroin solution. Subsequently, the solution is dialyzed in deionized water using a dialysis bag (molecular weight cutoff of approximately 3500 Daltons or equivalent) until bromide is obtained. The residual ions are less than 0.01% (detected by ion chromatography or conductivity); the regeneration steps include antisolvent precipitation or pH-induced regeneration, and finally, the particle dispersion system is obtained by ultrasonic or homogenization treatment to obtain regenerated silk fibroin nanoparticles. The particle size is precisely controlled by the antisolvent volume, stirring rate, temperature and addition rate; to ensure long-term storage stability, natural cross-linking or enzymatic cross-linking treatment can be performed on the surface of the nanoparticles. The cross-linking agent can be a natural source such as kaempferol or pectinase cross-linking product. If a chemical cross-linking agent such as glutaraldehyde is used, the residue should be strictly controlled and completely removed in the post-processing steps.
[0031] For the selection and formulation of antioxidant components, it is preferable to combine tea polyphenols (represented by epigallocatechin gallate) with vitamin E (tocopherol or tocopherol acetate). Tea polyphenols have good aqueous antioxidant properties and can be directly dissolved in the aqueous phase or loaded with silk fibroin particles to achieve sustained release. Fat-soluble components such as vitamin E should be dissolved in the oil phase or embedded in oil droplets to improve the stability of the formulation. The typical usage range is 0.05% to 1.0% for tea polyphenols and 0.01% to 0.3% for vitamin E. The specific content should be optimized based on the results of free radical scavenging efficiency, stability, and irritation tests. To ensure the stability of the components, it is recommended to add them in the dark and at low temperatures during production, and to add an appropriate amount of antioxidant cofactor (such as a trace amount of acidic buffer system) to the final product to inhibit oxidative degradation. It is recommended to quantify the antioxidant content and release curve by high performance liquid chromatography and verify the synergistic effect by free radical scavenging experiments.
[0032] This invention preferably uses a combination of sodium hyaluronate and ceramide as a moisturizing and barrier repair aid. The content of sodium hyaluronate in the formulation is generally 0.01% to 1.0%, preferably 0.05% to 0.5%, which increases the water content of the stratum corneum and forms an aqueous viscoelastic network through its strong water absorption properties. The content of ceramide is generally 0.01% to 0.5%, and its cationic nature helps to bind to the loaded silk fibroin particles or damaged skin surface and promotes the regeneration of the extracellular matrix. At the same time, ceramide has certain antibacterial activity and can reduce the risk of local infection. Glycerin, as a commonly used moisturizer, can work synergistically with hyaluronic acid. It is recommended that the content be below 1% to prevent the formulation from being too sticky. These components should be fully dissolved in the aqueous phase before the subsequent emulsification process, and the molecular weight of hyaluronic acid and the degree of deacetylation of chitosan should be clearly defined in the quality control to ensure consistency.
[0033] The preparation of the core-shell structure of the composite inorganic protective agent is one of the key technical points of this invention. For the core titanium dioxide, it is recommended to use a rutile or anatase crystal form with better skin safety, preferably rutile to reduce photocatalytic activity. The core particle size is recommended to be controlled between 15 and 200 nanometers to achieve good scattering efficiency and safety. The shell layer is made of silicon dioxide or zinc oxide. The silicon dioxide shell can be prepared by the tetraethoxysilane (hydrolysis condensation) sol-gel method. The molar ratio of tetraethoxysilane to the titanium dioxide surface coverage can be adjusted between 0.5:1 and 5:1. The ammonia concentration (catalytic system) is recommended to be maintained at 0.1% to 5% by volume. The reaction temperature is 10–40°C, and the reaction time is 0.5–6 hours to obtain the desired shell thickness (5–50 nm). The surface is further modified with organosilane coupling agents such as methyltriethoxysilane to introduce organic groups and reduce hydrophilicity / photocatalytic activity. The amount of coupling agent is 0.05%–2.0%, and the reaction is carried out under solvent and mild alkaline conditions. For the zinc oxide shell, deposition or co-precipitation methods can be used. After treatment, the composite particles should be washed, neutralized, and dried for storage. If necessary, the oxygen permeability stability and light-induced reactive oxygen species yield on the particle surface should be measured to verify the effect of the shell in inhibiting photocatalysis.
[0034] Silk fibroin at a concentration range of 0.03% to 0.1% can ensure its biological functions of film formation and promoting moist healing, while avoiding the increased viscosity, component compatibility issues, or cost increases caused by high concentrations of silk fibroin. It is recommended to use 0.03% to 0.08% as the initial experimental range for industrial preparation, and determine the optimal dose-effect curve through in vitro and in vivo healing and skin irritation tests. The functionality of silk fibroin can be supported by data from in vitro keratinocyte migration experiments, epidermal regeneration models, and animal models of wound healing.
[0035] The Sp1 degumming step uses a 0.02%–0.5% sodium carbonate aqueous solution at a temperature of 85–95 degrees Celsius for 30–60 minutes. After degumming, the solution is washed multiple times with deionized water until neutral and filtered through a cloth or mesh screen to remove residue. The Sp2 dissolution step preferably uses a 9.3 mol / L lithium bromide solution stirred at 60–80 degrees Celsius for 2–4 hours. This is followed by dialyzing in a large volume of deionized water using a dialysis bag (cutoff value approximately 3500 Daltons) for 48–72 hours, changing the water at least 6 times until conductivity is reached. The concentration and bromide ion residue meet the standards, and then the solid content is concentrated to 1%–5% by vacuum concentration or membrane separation; Sp3 When preparing silk fibroin nanoparticles with antisolvent, ethanol, acetone or isopropanol can be selected as the antisolvent, and the volume ratio (antisolvent: silk fibroin solution) is controlled at 1:1 to 10:1. It is added dropwise at a rate of 0.1–5.0 mL / min by a constant speed drop pump and stirred at 500–3000 rpm. The temperature is controlled at room temperature to 10 degrees Celsius to obtain a narrower particle size distribution. Then, 0.01%–0.5% of natural crosslinking agent (if kaempferol or pectin derivative is used) is added and reacted at room temperature for 0.5–6 hours. If necessary, 0.01%–0.1% of low concentration glutaraldehyde (with strict residue detection) is used as the crosslinking agent. After the reaction, sodium thiosulfate or other reducing agents are used to terminate the crosslinking and the particles are washed; Sp4 The sol-gel coating of titanium dioxide core-shell particles is carried out according to the above formulation parameters, and after preparation, it is washed several times with ethanol and water to remove residual catalyst and unreacted products; Sp5 The steps of Sp3 are carried out. The particles obtained from Sp4 are uniformly mixed in the aqueous phase. After the oil phase (stearic acid, lanolin, and dimethicone) is melted at 70–85°C, emulsification is performed using a high-shear homogenizer at 5000–15000 rpm for 5–30 minutes. After cooling to below 40°C, the pH is adjusted to 5.5–7.0 with triethanolamine to form a stable cream system. For Sp6, antioxidants, preservatives, and moisturizing agents are added sequentially at temperatures below 40°C and mixed thoroughly. Finally, the mixture is packaged in a sterile or low-contamination environment. Key scale-up parameters, including shear rate, emulsification temperature, particle dispersion energy, antisolvent addition rate, and final solids content, need to be optimized through experimental design during process transfer to establish the control range of key process parameters.
[0036] This product is used for local protection and repair of irradiated sites during and after radiotherapy. Patients with mild radiation dermatitis (grade I, early grade II) can apply a thin layer of this preparation 1-2 times daily after cleaning and drying the skin following radiotherapy, with each application being approximately 0.5-3.0 mg / cm². For wounds with exudation or blisters, the current principle is to follow the clinician's treatment guidelines for large areas of exudate or ulcerated wounds. This preparation can be used to maintain a moist healing environment and provide protection after appropriate treatment. Whether to apply the product on the day of radiotherapy should be in accordance with the radiologist's instructions. If the radiotherapy plan requires a clean surface, this should be followed to avoid image or dose deviations. This product can also be used for long-term barrier maintenance after radiotherapy, and it is recommended to use it in conjunction with strict sun protection and physical protection. The recommended storage conditions for this preparation are: store in a cool, dry place (15-25 degrees Celsius), away from light, and use within the time recommended on the label after opening. It is recommended to use light-resistant squeeze tubes or sterile press bottles for packaging to reduce contamination and the amount of preservatives used.
[0037] To ensure batch consistency and safety, the following tests are performed before product release: dynamic light scattering method to determine the average particle size and polydispersity index of silk fibroin nanoparticles; scanning electron microscopy or transmission electron microscopy to observe particle morphology and core-shell structure; infrared spectroscopy to identify the chemical bonds and component interactions of silk fibroin; X-ray diffraction to identify the crystal form of inorganic particles; high performance liquid chromatography to quantify the content of tea polyphenols and vitamin E and degradation products; ion chromatography or conductivity to determine bromide residues; total microbial count and pathogenic bacteria limit testing to ensure microbiological safety; preservative efficacy testing to verify the effectiveness of the preservative system; accelerated aging (40°C / 75% relative humidity) and long-term stability (25°C) tests to evaluate appearance, pH, particle size, and stability of active ingredients; and in vitro light-induced reactive oxygen species testing to demonstrate the photocatalytic inhibition effect of the composite inorganic particles. Quality standards should refer to relevant national regulations on topical preparations and supplement the corresponding regulatory requirements in the specific product positioning (cosmetics / medical devices / topical drugs).
[0038] When scaling up from laboratory to industrial production, key control measures must be implemented for material batches, solvent recovery and discharge, crosslinking agent residue, particle dispersion energy, energy input and cooling profiles of emulsification equipment, workshop cleanliness and personnel protection. Batch records and monitoring ranges for critical process parameters should be established to ensure product consistency. For versions intended for clinical applications, it is recommended to conduct skin tolerance tests, patch tests, and preclinical animal healing model validation concurrently in early trials to prepare the data required for subsequent clinical studies and registration. Specific Implementation Example 2: Cream-type formula (percentage by weight): Silk fibroin (regenerated silk fibroin nanoparticles) 0.05%; stearic acid 6.0%; lanolin 6.0%; polyethylene glycol 400-6.0%; triethanolamine 0.5%; dimethicone 2.0%; titanium dioxide@silica composite particles 8.0%; epigallocatechin gallate 0.5%; sodium hyaluronate 0.2%; methylparaben 0.05%; propylparaben 0.02%; balance: water.
[0040] Preparation steps: Degumming of silkworm cocoons: Place dried silkworm cocoons in a 0.05% to 0.5% sodium carbonate aqueous solution and boil at 90 degrees Celsius for 30 to 60 minutes. Remove and wash with water until neutral, then dry for later use. Dissolution and dialysis: Add dried silk fibroin to a lithium bromide solution of 9.3 mol / L and stir at 65–80°C for 2–4 hours to dissolve, obtaining a silk fibroin solution; place the solution in a dialysis bag and dialyze with a large amount of deionized water until the residual salt content is below the detection limit, then concentrate to a solid content of about 1%–5%; Preparation of silk fibroin nanoparticles: Ethanol was slowly added dropwise to the silk fibroin solution at a volume ratio of 1:1 to 1:10 at room temperature, and the mixture was stirred at 500 to 2000 rpm to form nanoparticles; 0.05% to 0.5% of a natural crosslinking agent (tannic acid or kaempferol) was added and the reaction was carried out for 1 to 3 hours to improve stability. Preparation of composite inorganic particles: Titanium dioxide nanopowder was dispersed in ethanol by ultrasonic dispersion, tetraethoxysilane was added as a silicon source, and hydrolysis and condensation were carried out for 0.5 to 6 hours under alkaline catalysis (ammonia water volume fraction 0.1% to 5%) to form a silica shell; the obtained particles were treated with organosilane coupling agent, washed, and dried. Emulsification: Prepare an oil phase (stearic acid, lanolin, dimethicone) at 70–85 degrees Celsius. Slowly add the oil phase to an aqueous phase containing silk fibroin nanoparticles and composite inorganic particles. Emulsify for 5–30 minutes at 5000–15000 rpm using a high-shear emulsifier. Cool and adjust the pH to 5.5–7.5 with triethanolamine. Subsequent additions: Add antioxidants (epigallocatechin gallate), sodium hyaluronate, preservatives, etc. at a temperature below 40 degrees Celsius, mix well and dispense.
[0041] Quality and Characterization: Average particle size of silk fibroin nanoparticles: approximately 50–300 nanometers; The average particle size of the titanium dioxide@silicon dioxide composite particles is approximately 15–200 nanometers, and the shell thickness is approximately 5–30 nanometers. Final cream appearance: uniform and smooth, with no visible phase separation, and pH value between 5.0 and 8.0. Specific Implementation Example 3: Gel-type formula: Silk fibroin nanoparticles 0.03%; hydroxyethyl cellulose or carbomer as gel matrix 0.5%–2.0%; epigallocatechin gallate 0.3%; titanium dioxide@silica composite particles 3.0%; sodium hyaluronate 0.1%; preservatives and water as the balance.
[0043] The key points of preparation are as follows: First, prepare an aqueous phase of silk fibroin nanoparticles, dissolve and cross-link the gelling agent into a gel network, then uniformly disperse the silk fibroin nanoparticles and composite particles into the gel, add antioxidants and preservatives at low temperature, and then package them. Specific Implementation Example 4: Key quality control indicators: Average particle size of silk fibroin nanoparticles: 50–300 nm; average particle size of titanium dioxide@silica composite particles: 15–200 nm; residual pyrolysis salts (such as bromide residues) below the detection limit or less than 0.01%; system pH: 5.0–8.0; viscosity (25 degrees Celsius, specific shear rate): set within a suitable range according to the dosage form; target retention rate of active ingredients ≥90% after 3 months of accelerated aging; microbiological indicators meet the relevant national standards for pharmaceuticals or cosmetics (depending on the end-use category).
[0045] Clinical application, contraindications and precautions: Applications: Skin protection and care during and after radiotherapy, especially suitable for local care of mild to moderate radiation dermatitis and barrier maintenance of chronic radiation dermatitis; Contraindications: This preparation is contraindicated in patients with known hypersensitivity to any of its components. In cases of deep infection, progressive tissue necrosis, or severe ulcers requiring surgical debridement, caution should be exercised under the guidance of a clinician, or surgical intervention should be performed first. Precautions: If used on the day of radiotherapy, please strictly follow the radiologist's instructions regarding whether topical preparations are permissible before treatment; if significant adverse reactions or allergies occur, discontinue use and seek medical attention; this product is for external use only, avoid accidental ingestion or contact with eyes. Specific Implementation Example 5: like Figures 1 to 4 As shown, further experimental testing systems were developed to evaluate the protective effect of the silk fibroin skin protectant of the present invention on acute and chronic radiation dermatitis and its skin repair effect, and to verify the safety, moisturizing, sun protection and antioxidant capacity of the formulation.
[0047] Main components and content (by mass percentage): Silk fibroin nanoparticles: 0.05%, particle size approximately 120±10nm; Stearic acid: 8%; Lanolin: 8%; Polyethylene glycol 400: 5%; Triethanolamine: 0.8%, used to adjust pH to 6.5; Dimethicone: 3%; Core-shell composite inorganic protective agent (TiO2@SiO2, core particle size 30nm, shell thickness 15nm): 10%; Tea polyphenols (antioxidant): 0.5%; Sodium hyaluronate (moisturizing and barrier repair): 0.2%; Methylparaben and propylparaben (preservatives): 0.05% each; Balance: Water.
[0048] Preparation of silk fibroin nanoparticles: Silkworm cocoons were boiled in a 0.05% sodium carbonate aqueous solution at 90℃ for 45 minutes to degummify, and then washed with deionized water until neutral. The degummed silk fibroin was dissolved in a 9.3M lithium bromide solution at 60℃ for 3 hours. Dialysis was performed for 72 hours, with the water changed 6 times to remove salts. Ethanol (antisolvent) was added dropwise to the silk fibroin solution at 1 mL / min, and the mixture was stirred at 1000 rpm to form nanoparticles with a particle size controlled at approximately 120 nm.
[0049] Preparation of core-shell composite inorganic protective agents: TiO2 nanoparticles (30 nm) were used as the core, and a silica shell (approximately 15 nm thick) was coated using a tetraethoxysilane sol-gel method. The reaction temperature was 25 °C, and ammonia was used as the catalyst. The shell was uniformly covered, which reduced the photocatalytic activity.
[0050] Cream preparation: Oil phase: stearic acid, lanolin, and dimethicone are heated to 75°C and melted.
[0051] Aqueous phase: silk fibroin nanoparticle dispersion, composite inorganic particles, water heated to 75℃.
[0052] Add the aqueous phase to the oil phase, emulsify at high shear rate of 10,000 rpm for 10 minutes, adjust the pH to 7.0, cool to below 40 degrees Celsius, add preservatives, polyethylene glycol 400, sodium hyaluronate, and tea polyphenols, and stir until homogeneous to obtain the finished product.
[0053] Nanoparticle size: 120±10nm (DLS measurement); PDI: 0.21; Zeta potential: -25mV; Core-shell particle characterization: SEM / TEM showed that TiO2 cores uniformly coated with SiO2, with a shell thickness of 15nm; UV blocking rate (280–400nm) >95%; Photocatalytic activity (reactive oxygen generation): decreased by 80%.
[0054] Animals: Acute radiation dermatitis on the back of a mouse: X-ray irradiation 20 Gy; Groups (n=10): Control group (no treatment), basic cream group (no silk fibroin), and invention group (silk fibroin protective agent); Usage: Apply twice daily for 14 consecutive days; Histological analysis: The dermal inflammatory cell infiltration was significantly reduced in the group of this invention, the epithelial repair was more complete, and the capillary dilation was improved.
[0055] Chronic radiation dermatitis test: Subjects: 20 patients with dry skin and pigmentation after radiotherapy; experimental group (the preparation of this invention) and control group (vitamin E cream); applied twice daily for 8 weeks; Skin irritation test: No redness, swelling, or itching; Microbiological test: Meets the standards for topical preparations; Storage stability: No precipitation or discoloration after 6 months at 25℃; This embodiment demonstrates that the silk fibroin skin protectant of the present invention can significantly alleviate the symptoms of acute radiation dermatitis and accelerate skin repair; improve dry skin and pigmentation in chronic radiation dermatitis and prevent ulcer formation; the silk fibroin nanoparticles, core-shell composite inorganic protectant and antioxidant work synergistically to moisturize, protect against sun, resist oxidation and repair the skin barrier; it has high safety and is suitable for long-term use in clinical practice and during radiotherapy.
[0056] It should be noted that, in this document, relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising a reference structure" does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes the element.
[0057] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A silk fibroin skin protectant, characterized by, By mass percentage, the following components are included: Silk fibroin or silk fibroin micro- or nano-particles 0.01% to 0.5%; Stearic acid 1% to 15%; Lanolin 1% to 15%; Polyethylene glycol 400-1% to 15%; Triethanolamine 0.1% to 2%; Dimethicone 0.5% to 10%; Composite inorganic protective agent 1% to 25%, which is a core-shell or composite particle with titanium dioxide as the core and silica or zinc oxide as the shell, with a particle size range of 10 to 800 nanometers; Antioxidant active ingredient 0.01% to 2%, which is tea polyphenol, vitamin E or its derivatives; Moisturizing and barrier repair aid 0.01% to 2%, which is sodium hyaluronate, ceramide, glycerol or their combination; Preservative, including methyl paraben 0.01% to 0.2%, propyl paraben 0.01% to 0.2%; The balance is water, keeping the pH of the preparation between 5.0 and 8.
0.
2. The silk fibroin skin protectant of claim 1, wherein: The silk fibroin is a natural silk fibroin fiber obtained after degumming of mulberry silk, or a regenerated silk fibroin obtained after the steps of dissolution, dialysis and regeneration.
3. The silk fibroin skin protectant of claim 2, wherein: The antioxidant active ingredient is one or more of tea polyphenol, epigallocatechin gallate, quercetin or vitamin E.
4. The silk fibroin skin protectant of claim 1, wherein: Further comprising 0.01% to 1% of ceramide or sodium hyaluronate for enhancing skin barrier repair and moisturizing performance.
5. The silk fibroin skin protectant of claim 1, wherein: The composite inorganic protective agent has a core-shell structure, with titanium dioxide as the core and silica or zinc oxide as the shell, a shell thickness of 5 to 50 nanometers, and the surface of the titanium dioxide is treated with an organosilane coupling agent to reduce photocatalytic activity.
6. The silk fibroin skin protectant of claim 1, wherein: The mass percentage of silk fibroin in the protective agent is preferably 0.03% to 0.1%.
7. A process for the preparation of a silk fibroin skin protectant according to any one of claims 1 to 6, characterized in that, The following steps are included: Sp1. Boil the cocoon in a sodium carbonate aqueous solution to remove the gum, and obtain the silk fibroin; Sp2. Dissolve the silk fibroin in a lithium bromide solution, dialyze to remove residual salts, and concentrate to the desired solid content; Sp3. Form silk fibroin nanoparticles by adding an anti-solvent to the silk fibroin solution, and add a natural crosslinking agent if necessary; Sp4. Prepare composite particles with a titanium dioxide core and a silica or zinc oxide shell, and control the shell thickness under alkaline conditions; Sp5. Disperse the silk fibroin nanoparticles obtained in step Sp3 and the composite particles obtained in step Sp4 in an aqueous phase, emulsify with an oil phase, adjust the pH to form a cream or gel; Sp6. Add antioxidants, preservatives and moisturizing aids at less than 40 degrees Celsius, mix well to obtain the finished product.
8. Use of a silk fibroin skin protectant according to any one of claims 1 to 6, characterized in that: The silk fibroin skin protective agent is used to block ultraviolet radiation, reduce damage to the skin by active oxygen free radicals, repair the skin barrier and maintain the water content of the skin, and is used in creams, sprays, masks, gels or other external skin protective preparations.